Formulation and evaluation of topical anti-fungal gel containing Itraconazole - Mehta, Roshan Kumar; Yadav, Ganesh Kumar; Kunwar, Mausami; Chaudhary, Pankaj; Gupta, Suraj Kumar; Palikhey, Anjan; Mehta, Vivek Kumar (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Topical delivery was selected to enhance localized drug concentration at the site of infection while minimizing systemic side effects. Itraconazole makes the fungal cell membrane weak, leading to leakage of cell contents and ultimately fungal cell death. The present study focused on the formulation and evaluation of a topical antifungal gel containing itraconazole for the effective treatment of superficial fungal infections. Methods: The gel was prepared using suitable gelling agents such as Carbopol 940 and HPMC K4M, with Dimethyl Sulfoxide as a solvent and propylene glycol as a co-solvent. The formulation was optimized based on parameters including pH, spreadability, drug content and in vitro drug release. Antifungal efficacy was assessed using the agar well diffusion method against Candida albicans. The optimized formulation showed desirable physiochemical properties, sustained release, and significant antifungal activity, suggesting its potential as an effective topical treatment for fungal skin infections. Results: The results showed that the F7 formulation was found to be optimal, showing a skin-compatible pH of 6.43±0.025, good spreadability (10.84±0.1035), high drug content, and a sustained drug release profile reaching up to 93.07% over 240 minutes. Conclusions: The study successfully developed an optimized Itraconazole topical gel using Carbopol 940 and HPMC K4M. Among the formulations, F7 exhibited the best physicochemical properties and in vitro drug diffusion. These results confirmed23 that the developed gel is an effective delivery system for treating and preventing fungal infections.